A new supporting phase system for producing antibacterial and regenerative dental composite fillings
Patent Information
- Application Number
- JP2024536375
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-12-05
- Publication Date
- 2025-02-19
Smart Images

Figure 2025504751000001 
Figure 2025504751000002
Abstract
Description
[Technical field]
[0001] The present invention relates to light curable and polymerizable restorative acrylic dental composite fillings and a novel supporting phase system for producing dental composites and the production of novel acrylic dental composite fillings in the art. [Background technology]
[0002] Resin-based composites (RBCs) were first reported by Bowen in 1958. Meanwhile, commercial use of resin-based composites was made possible by the inventor's subject matter patent "a vinyl-silane treated fused silica and binder" in 1962. The concept of chemically hardened RBCs was only conceptualized after their introduction to the dental market in 1970. Meanwhile, their application without the use of abrasives in large-scale restorations is limited, but these materials are often preferred for Grade I and Grade II restorations.
[0003] The 1974 patent by Dart entitled "A method of repairing teeth using a composition which was curable by visible light" and the development of the "Total Etch" adhesive in the 1980s supported and paved the way for the clinical use of light-cured RBCs in Grade I and Grade II restorations.
[0004] In recent years, as expectations for aesthetic dentistry have increased, the development of clinically long-lasting resin composites with advanced physical and mechanical properties that meet the aesthetic needs has become essential for use in direct restorations. One of the most important developments in this field is the use of nanostructured particles in the structure of conventional resins by combining them with nanocrystals.
[0005] The history of the existing resin monomers is based on the discovery of a new acid called "acrylic acid" by the German chemist J. Redtenbacher. In the 1900s, in addition to the synthesis of methacrylic acid and many ester derivatives, methyl methacrylate polymers were also produced by polymerization techniques. In the late 1930s, polymethyl methacrylate was first introduced into the dental field as a denture base resin, and a few years later, it was used as an indirect filling material. The discovery of the benzoyl peroxide-tertiary amine redox initiator-accelerator system in Germany during World War II made it possible to carry out the polymerization of methyl methacrylate at room temperature, and therefore to use these polymer structures as direct filling materials. On the other hand, these materials could not meet the necessary clinical expectations.
[0006] Observing the insufficient properties of methyl methacrylate resins, the American dentist RL Bowen also developed other synthetic resins for use in dental fillings. In this context, RL Bowen carried out research on epoxy resins that can be polymerized at room temperature. Epoxy resins exhibit excellent aesthetic properties in the oral cavity, but due to their slow hardening phase they cannot be used directly as filling materials.
[0007] In response to problems encountered with epoxy resins, Bowen conducted research on a new monomer system, the 2,2-bis[4-(2-hydroxy-3-methacryloxypropoxy)phenyl]propane-BisGMA structure, in 1956. This monomer system has been found to be significantly superior to methyl methacrylate systems due to its high molecular weight, chemical structure, low volatility, low polymerization shrinkage, and rapid curing properties.
[0008] BisGMA has been found to be widely used in commercial dental resin composites. On the other hand, the color stability of the monomer was insufficient, the viscosity was high, and it could not be purified by methods such as distillation and crystallization. To prevent this problem, Bowen had been conducting research on a new monomer system, isomeric crystalline dimethacrylates, which exhibit eutectic formation and are liquid at room temperature. In this context, bis(2-methacryloxyethyl)-P / I / T ester monomers were synthesized from three aromatic diesters of phthalic acid (P), isophthalic acid (I), and terephthalic acid (T) and purified by a recrystallization method. The mechanical properties of the composites produced from these monomers were determined to be comparable to BisGMA, and the polymerization shrinkage values met the expected properties. On the other hand, these monomer systems could not provide the expected color stability in vivo.
[0009] Depending on the polar structure, dimethacrylate resins tend to adsorb moisture in the oral environment and exhibit hygroscopic expansion. This expansion, which has some advantages, in the long term causes various disadvantages, such as a decrease in mechanical strength and wear resistance. For this reason, hydrophobic monomer systems obtained by removing the hydroxyl groups in the BisGMA chain were developed to minimize the water-holding capacity of the resin. However, these systems could not meet the desired mechanical properties.
[0010] As the expected properties of hydrophobic monomers were not met, various studies were carried out to develop fluorocarbon-containing polymers with low surface energy and high hydrophobic properties. In this context, polyfluoromonomethacrylate and octafluoropentyl methacrylate monomer systems were used in resin composites. These composite structures provide the expected hydrophobicity against water, but do not provide sufficient physical and mechanical properties and exhibit rather high polymerization shrinkage.
[0011] Another monomer system used in composite resins, urethane dimethacrylate (UDM), was initially synthesized from hydroxyalkyl methacrylates and diisocyanates. This monomer has a similar molecular weight to BisGMA but lower viscosity values. The monomer conversion of composite systems made with UDM monomers is higher than that of BisGMA systems, ensuring higher biocompatibility. These systems are used as replacements for BisGMA monomers in commercial resin composites depending on their economics.
[0012] Polymerization shrinkage is the most common problem in composite resins. The approximate volumetric shrinkage of BisGMA-based polymers is about 5%, but this value can be reduced by increasing the amount of the support phase system added. Since polymerization shrinkage is one of the important parameters that affect the service life of composites, various studies have been conducted on non-shrinking compounds and polymerized bicyclic compounds by ring-opening polymerization methods. Bailey stated that various bicyclic monomers and unsaturated dicetels, including spiro orthocarbonates, spiro orthocarbonates, bicyclic ketolactones, and trioxabicyclooctanes, exhibit double ring polymerization without shrinkage and / or expansion. Meanwhile, at the end of the reaction, it was found that there were many monomers in the environment that were not added to the polymer structure.
[0013] After the development of organic resin structures, in 1994 polyacid-modified composites known as "compomers" were produced. These composites are obtained by embedding a supporting phase system, such as calcium-aluminum-fluorosilicate glass, in a polymer resin. Compomers are dental materials that combine the aesthetic properties of traditional composites and the fluoride-releasing and adhesive properties of glass ionomer cements. In contrast, compomers are separated from glass ionomer cements in two ways: first, the glass particles are partially silanized to allow bonding with the resin; second, the monomers are activated by light, which causes a radical polymerization reaction, resulting in the formation of a polymer structure.
[0014] In 1984, Schmidt synthesized the first organic-inorganic polymer hybrid structures called "ormosils" (organically modified silicates) and later "ormocers" (organically modified ceramics). In ormocers, organic and inorganic compounds are combined at the nanoscale, i.e. molecular scale. Because of this, these materials exhibit unique characteristics, the causes of which are not yet understood, despite having the properties of organic and inorganic components in their structure [9]. Ormocers began to be used in dentistry in 1998 and have found commercial use, especially in restorative material applications in recent years.
[0015] One of the recent technological developments in commercial dental materials is the use of silorane-based organic resin monomers. Silorane monomers are named for the siloxane and oxirane molecules that compose their structure. Developed in 3M ESPE to reduce polymerization shrinkage and obtain composites that maintain adequate mechanical strength, silorane monomers are expected to become alternatives to methacrylate-based monomers and may find commercial application in the short term, depending on whether they meet the desired clinical expectations.
[0016] In addition to reducing polymerization shrinkage, another feature that is desired to introduce into monomeric systems is an antibacterial effect. In this context, instead of adding fluoride-releasing compounds to the structure, monomers have been produced that exhibit antibacterial properties. In this context, the most promising monomer is methacrylyldodecilpyridinium bromide (MDPB), which is produced by reaction of the antibacterial agent dodecylpyridinium bromide with a methacrylate group. Various studies have found that composite systems produced as a result of copolymerization of traditional dental monomers with methacryldodecilpyridinium (MDP) have an inhibitory effect on bacterial formation on surfaces. On the other hand, in the composite systems currently produced commercially, the antibacterial effect is not provided via such monomeric systems, but is realized through fluoride-releasing support phase particles.
[0017] In the 1960s, three basic materials were used in the construction of the first composite resins: monomer, silanized supporting phase, and initiator. The supporting phase used by Bowen in 1963 consisted of crushed quartz particles with an average size of 8-12 μm (8000-12000 nm). Due to limitations of macrophilic composites in aesthetic restorations (e.g. problems with surface polishing), minifill composites were developed in the 1970s. Support phase systems produced by pyrogenic methods allowed the addition of up to 55% to the composite, which improved polishing ability but significantly reduced mechanical strength.
[0018] Only in the 1980s and 1990s could the support phase systems be tested only as mixtures. These restorative materials, including hybrid support phase systems with particle sizes of 600-2,000 nm, have been commercialized as hybrid, microhybrid, and condensed (whisker structure) composites. In these products, the mechanical strength has increased significantly, but the abrasiveness is still limited. In these products, the maximum loading rate reached 70-77% by weight. However, the particle size values of the conventional composites could not provide sufficient harmony with the hydroxyapatite crystals, dentin tubules, and enamel corpuscles in the natural structure of the tooth. Therefore, the possibility of providing the necessary adhesion between the macro-level restorative material and the nano-level (1-10 nm) tooth structure could not be obtained.
[0019] Since it is impossible to produce a support phase smaller than 100 nm by milling methods, the use of support phase production, nanotechnology methods by offering features such as controlled crystal growth, homogeneity of the final product in terms of structure and size, have become a revolutionary technology in this field. At the beginning of this century, Filtek Supreme (3MESPE, St. Paul, USA) has become a commercial turning point for the application of nanotechnology in surgical dentistry. In this context, the composite resin produced contains 78.5% agglomerated (aggregated) zirconia / silica clusters with a main particle size of 5-20 nm and a silica-based support phase system with a particle size of 20 nm without agglomerates.
[0020] Recently, composite systems including microhybrid and nanophilic composites have been commercialized. These new compositions allow the loading of the support phase system to be increased by up to 87% by weight due to the formation of filler cavities between the larger and smaller particles of the support phase content.
[0021] The curing techniques used to polymerize composites have also evolved in response to developments in the support phase and monomer systems. As previously mentioned, the first composite fillings used in dentistry were polymerized by a redox reaction at room temperature. The polymerization reaction of these products, packaged as two separate materials, took as long as 8 minutes to properly complete polymerization, starting with the mixing of the products.
[0022] Depending on the length of the polymerization period, light-polymerizing composite systems (Nuva; Dentsplay / Caulk) were developed in the late 1970s. Such polymerization methods offered the dentist the advantage of rapid curing after placement of the product and the ability to create the desired contour. These systems initially used a quartz lamp with a wavelength of 354 nm as a UV light source to drive the polymerization reaction through the formation of free radicals. Although this system was initially advantageous, in the subsequent period, various problems arose, such as polymerization not being fully realized when used intensively, and the exhaustion of the light source being encountered very quickly. For this reason, in the subsequent period, the application of visible light energy in the wavelength range of 400-500 nm was started instead of ultraviolet light for photopolymerization. In the visible light systems, a quartz-tungsten-halogen light source was first used. The most commonly used photoinitiator system in these systems is camphorquinone. The polymerization time for a 2 mm thick restoration using a conventional quartz-tungsten-halogen light source takes approximately 40-60 seconds. These systems have advantages for polymerization compared to self-curing systems, but the light energy on the surface of the composite is stronger than in the underlying areas, and the light penetrates the lower areas to a lower intensity, so new methods are being sought.
[0023] Dental applications have also improved with the development of laser technology that provides high light intensity in the energy band range required for photopolymerization of dental materials. The "Argon laser" provides high energy output at a wavelength of 448 nm, which offers various advantages such as rapid polymerization in commercially available dental restorative materials.
[0024] Another system developed to reduce polymerization times is the "plasma arc unit". In this context, the short arc system provided by the use of a xenon light source is called the plasma arc source. This unit consists of a spark generated by applying a high-energy potential between two tunnels and a fluid gas system. This system operates at a wavelength of 400-500 nm and the polymerization takes place in less than a second. On the other hand, some researchers suggest that the polymerization occurs so quickly that the characteristics of the final product do not have the desired quality.
[0025] To keep quartz-tungsten-halogen lamps on the market, manufacturers developed existing systems by providing "high energy" output and short application times similar to plasma arc systems. Meanwhile, the development of fast curing conditions raised concerns about polymerization shrinkage.
[0026] The developments seen in light-emitting diode (LED) technology have made the use of these light sources essential in the dental industry. The absorption range of blue LED light sources corresponds to the wavelength range of dental photoinitiator systems. The main advantages of this light source include portability, minimal maintenance requirements, long life, and absorption only at the wavelengths required for photoinitiator activation. Another curing method used especially in cement technology is the dual cure method. Since chemical curing requires removing excess initiators remaining in the environment from the environment and waiting for a long time until the product is completely stable, attempts have been made to solve this problem by light curing. On the other hand, light curing does not allow light to reach deep enough to achieve complete polymerization. To prevent these problems, dual cure resin cement systems have been developed by using both chemical and photoinitiator systems in the product.
[0027] One of the most important cases in composite restorations is monomer conversion. One of the easiest ways to achieve polymerization is by adding heat. It is observed that heat reduces the viscosity of the monomer, allowing free radicals to diffuse better into the monomer, resulting in higher monomer conversion. Based on this principle, a "post-cure heat" method was developed for photoinitiated composite systems. In this method, the composite is first cured with a conventional light source to photopolymerize, and then heat is added. This method is preferred for glass ionomer systems over composite fillings.
[0028] Starting from methyl methacrylate resin composition, resin-based composite restorations have been developed in terms of organic resin, inorganic phase, and curing technology. Meanwhile, resin-based composite fillings do not have a structure that can mimic the structure of natural teeth, and do not have sufficient characteristics to meet clinically required expectations. Therefore, research on the development of composite filling properties continues at an ever-increasing pace as clinical expectations.
[0029] In 2014, Martin et al. conducted a study on the synthesis of a urethane multimethacrylate-based monomer system that could be an alternative to BisGMA-based composites, which suffer from problems such as low monomer conversion and high volume shrinkage. In this context, the researchers produced a urethane multimethacrylate monomer using methacryloyloxypropylphenylmethane (BMPM) and urethane methacryloyloxyethyl (UME) initial monomers. By adding silica support phase particles to this monomer system, the produced composite showed low polymerization shrinkage and high bending strength compared to conventional composites, revealing that the physical, chemical, and mechanical properties of the composite have a certain balance.
[0030] Liu et al. focused on the problem of uniformly dispersing Ag nanocrystals in organic resins used in dental composites to prevent secondary caries formation, and added silver particles to the composite system by modifying them with organic agents. In this context, Ag nanoparticles were coated with oleic acid to investigate the mechanical and antibacterial properties of dental resin composites. The researchers found that the modified silver nanoparticles significantly improved the mechanical and antibacterial properties of the composites, such as flexural strength, elastic modulus, and compressive strength, compared to unmodified particles.
[0031] He et al. conducted a study on the synthesis of antibacterial and radiopaque dimethacrylate monomers for use in dental resin composites. In this context, the researchers synthesized tertiary ammonium dimethacrylate compounds such as N,N-bis[2-(3-(methacryloyloxy)propanamido)ethyl]-N-methyldodecylammonium iodide (QADMAI-12), N,N-bis[2-(3-(methacryloyloxy)propanamido)ethyl]-N-methylhexadecylammonium iodide (QADMAI-16), and N,N-bis[2-(3-(methacryloyloxy)propanamido)ethyl]-N-methyloctadesethylammonium iodide (QADMAI-18). The researchers revealed that the produced composites not only had superior monomer conversion rates compared to conventional composites, but also superior antibacterial and radiopaque properties. Meanwhile, the flexural strength and modulus values of the composites were observed to be lower than the conventional composites.
[0032] Liu et al. conducted a study on light-cured antibacterial dental resin composites. They added a support phase system, prepared by combining poly(BisGMA)-grafted silanized whisker hydroxyapatite (PGSHW) with silanized silica (s-SiO2) nanoparticles, to a bisphenol A glycidyl methacrylate (BisGMA) / triethylene glycol dimethacrylate (TEGDMA)-based dental resin. The researchers found that the composites containing the prepared PGSHW / s-SiO2 hybrid support phase system had significantly improved values of flexural strength, elastic modulus, compressive strength, and toughness, as well as monomer conversion rate, compared with the composites containing hydroxyapatite nanoparticles. Furthermore, they showed that the prepared composites were capable of forming apatite by in vitro bioactivity tests.
[0033] Wu et al. developed a self-healing composite containing dimethylaminohexadodecyl methacrylate (DMAHDM) to provide antibacterial function and nano-sized amorphous calcium phosphate (NACP) for remineralization, and found a solution to problems such as cracks and secondary caries occurring in composite restorations. As a result of the research, it was described that this composite structure, which was produced for the first time in the literature, has the ability to repair cracks, has antibacterial effect, and remineralize after crack formation.
[0034] Similar to Wu et al., Chan et al. also conducted a study on composite systems with antimicrobial effects. They added nano-sized amorphous calcium phosphate ceramics and dimethylaminododecyl methacrylate (DMADDM) monomer structures to the organic resin system of a conventional composite. The results of these studies showed that the release of Ca and P ions increased in association with the decrease in pH as a result of bacterial growth, and that the DMADDM monomer exhibited an antimicrobial effect, thereby inhibiting bacterial growth, suggesting that these materials may be suitable for use as a supporting phase system in composites.
[0035] Similar to Chan et al., Zhang et al. used dimethylaminododecyl methacrylate (DMADDM), amorphous calcium phosphate nanoparticles, and silver nanoparticles (NAg) as the supporting phase system, which have antimicrobial effects, and revealed that the antimicrobial effect was longer compared to other composites.
[0036] Zhou et al. developed a new antimicrobial monomer system and added amorphous calcium phosphate nanoparticles to this system to prevent the formation of biofilms observed on the composite structures and the associated development of secondary caries. As an antimicrobial monomer, dimethylaminohexane methacrylate (DMAHM) monomers with six carbon chains were used to synthesize dimethylaminododecyl methacrylate (DMADDM) monomers with 12 carbon chains, similar to Chan and Zhang's study, and amorphous calcium phosphate nanoparticles (nACP) produced by spray drying technology were added as the supporting phase of this structure. The results of these studies revealed that the DMADDM monomer showed a higher antimicrobial effect compared to the DMAHM monomer. The researchers revealed that the DMADDM-NACP nanocomposite had similar strength values compared to the system using tertiary ammonium dimethacrylate, and biofilm formation on the composite was slightly reduced by 5%. Considering these findings, the researchers suggested that the length of the carbon chain of the monomer was very effective in the antibacterial activity.
[0037] Jan et al. focused on polymerization shrinkage, one of the most common problems in dental restorations, and aimed to reduce polymerization shrinkage and improve hardness values of composite structures by modifying dimethacrylate monomers with diisocyanate side groups. The results of the study showed that the use of diisocyanate side groups can reduce polymerization shrinkage and increase the surface hardness of composites depending on the chain length.
[0038] Khan et al. conducted a study to improve the bonding between filling materials and tooth interfaces and to result in fluoride release. In this context, nano-fluorapatite (nFA) particles produced by the sol-gel method were bonded to an organic resin consisting of a urethane monomer structure via diisocyanate side chains. The researchers revealed that the produced composite showed superior adhesion to tooth structures compared to conventional composites and released fluoride in the long term, suggesting the possibility of using this composite structure as a filling material.
[0039] Liu et al. investigated the morphology, loading, and mechanical properties of composites by adding silanized hydroxyapatite (DK-sHA) particles, which have a morphology similar to sea urchins, to composites with and without BisGMA / TEGDMA organic resin structures containing silica nanoparticles. They found that the mechanical properties of the composites could be improved by adding 5 and 10 wt% DK-sHA support phase to the silica-free composite structures, and that the modulus and microhardness values of the composites increased at the loading levels of 20% to 30%, but the strength did not increase further. They found that DK-sHA was embedded in the resin and was uniformly dispersed in the composites compared to silanized amorphous hydroxyapatite and whisker hydroxyapatite. It was found that the strength and modulus values of the composites could be significantly improved when the composites were added to the composite systems containing silica particles.
[0040] investigated the effect of alkaline bioactive glass nanoparticles (SiO2-Na2O-CaO-P2O5-Bi2O3) added to a dental resin on the composite properties. The researchers found that a 20% addition significantly increased the monomer conversion without having an effect on the microhardness.
[0041] Hojati et al. added ZnO nanoparticles to a composite to improve the antimicrobial effect of dental restorative materials and evaluated the physical and mechanical properties of the composite along with the antimicrobial effect of the composite against Streptococcus mutans. They found that with increasing addition of ZnO nanoparticles, bacterial development was significantly reduced, while flexural strength, compressive modulus, and monomer conversion values remained unchanged compared to the conventional composite system.
[0042] Jan et al. found a solution to the polymerization shrinkage problem of dental composites by modifying Bis-GMA monomer and adding toluene 2,4-diisocyanate (TDI) and 1,6-hexamethylene diisocyanate (HDI) functional side groups to this monomer system. They found that resins modified with TDI, containing higher functional side groups, showed lower cytotoxic effects than resins modified with HDI. Furthermore, they suggested that TDI-modified resins caused less toxic effects compared to BisGMA monomers due to the compaction of toxic resin monomers within the structure.
[0043] Teeth are organs that are involved in many systems, such as aesthetic appearance, speech, and digestion. Dental disease is described as a problem that directly affects the quality of life of an individual. Health problems occurring in teeth, especially dental caries, can not only negatively affect the performance of life functions, but also affect the economy of an individual and a country. Dental caries has been one of the most common diseases in the dental and oral environment from the past to the present. According to data from the World Health Organization, dental caries has been described as the most common non-communicable disease worldwide, after the common cold. The treatment of dental caries involves removing the deteriorated tissue from the structure and replacing it with a filling material that can perform the functions of the tooth, such as chewing and mastication. Various filling materials have been used from the past to the present, such as amalgam, glass ionomer, and composite, but the biggest problem seen with these materials is the deterioration of the composite filling-tooth bond due to secondary caries. For this reason, producing a composite that allows the prevention of secondary caries is one of the most researched challenges. The release of composites reinforced with various structures such as AlF3, Ag, MgO, ZnO, chlorhexidine (CHX), MDPB, glass ceramics used for this purpose, and the high loading rate, reduces the mechanical properties of the composite. Furthermore, secondary caries that have developed in the tooth may progress, making intervention necessary. Although various studies have been carried out with hydroxyapatite, there is no commercially available material that is regenerative and antibacterial, suitable for use in type 1 and type 2 restorations, as sufficient mechanical properties cannot be provided.
[0044] As a result, it is expected that the art will see innovations to minimize problems such as polymerization shrinkage and secondary caries formation in the manufacture of dental filling materials. Summary of the Invention [Problem to be solved by the invention]
[0045] The present invention relates to light curable and polymerizable restorative acrylic dental composite fillings and novel supporting phase systems for producing dental composite fillings, in order to eliminate existing shortcomings in the art and to provide further technical advantages and solutions in the art.
[0046] The primary object of the present invention is to provide an acrylic dental composite filling material with improved edge conformance by reducing polymerization shrinkage.
[0047] Another primary object of the present invention is to provide an acrylic dental composite filling having improved antibacterial and bioactive properties.
[0048] In another aspect, the present invention provides an acrylic dental composite filling that minimizes the formation of secondary caries in a patient.
[0049] The present invention aims in one aspect to provide an acrylic dental composite filling having improved regenerative properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0050] In this detailed description, the subject matter of the present invention relates to a new supporting phase system for producing a light-curable and polymerizable restorative acrylic dental composite filling and the dental composite filling, which is illustrated by means of examples that do not have any limiting effect, solely for a better understanding of the subject matter.
[0051] The present invention relates to a dental filling material that provides all these advantages described in the art. The dental filling material is a composite material. The composite filling material that can be used as a dental filling material includes a matrix that includes at least one organic component in the filling material, and a support phase system that includes components that provide antibacterial, regenerative, and bioactive properties to the final product.
[0052] The supporting phase system within the acrylic dental composite fillings of the present invention provides antibacterial properties to the final product and also contains components that have high mechanical properties.
[0053] The acrylic dental composite filling material of the present invention comprises biomimetic hydroxyapatite, Al-Sr-OF, and Al-Si-Sr-OF compounds, and a silica component as a supporting phase. The components contained in the supporting phase system of the present invention have nanoflower morphology, unlike current technology. The supporting phase system obtained from the components having nanoflower morphology has high surface area / volume properties. Furthermore, the supporting phase system has high surface reactivity due to the presence of components having these properties. Finally, the supporting phase system thus developed ensures that the performance of the resulting acrylic dental composite filling material is improved to a very high level.
[0054] The support phase system of the invention makes it possible to obtain highly antibacterial acrylic dental composite fillings thanks to the Al-Sr-OF and Al-Si-Sr-OF components with nanoflower morphology, which, thanks to the fluoride content, prevent the formation of secondary caries visible in the patient.
[0055] The supporting phase system of the present invention allows obtaining acrylic dental composite fillings with high biocompatibility and regenerative properties due to the biomimetic hydroxyapatite component with nanoflower morphology. In addition to the aforementioned properties, the biomimetic hydroxyapatite component also contributes to improving the flexural strength, compressive strength, hardness, cure depth and polymerization shrinkage properties of the final acrylic composite filling.
[0056] In this invention, we provide a method for producing each component within a supporting phase in the form of a nanoflower.
[0057] The supporting phase system of the present invention is present in the range of 50% by weight to 90% by weight in the dental composite filling material.
[0058] The inventors have been able to use three different methods to fabricate biomimetic hydroxyapatite components within the support phase system. These methods include microwave irradiation, sonochemical, and hydrothermal synthesis. Under this heading, the fabrication of hydroxyapatite components in nanoflower form by the above mentioned fabrication methods will be described in detail.
[0059] Synthesis of hydroxyapatite compounds in nanoflower morphology (NH4)2HPO4 and Ca(NO3)2.4H2O solutions are used as raw materials for the production of hydroxyapatite compounds. Furthermore, synthetic body fluids having compositions as known in the art are used. Thus, in the form of nanoflowers, the hydroxyapatite component is first composed in the following process steps: i. Add 50 ml of a mixture of Ca(NO3)2.4H2O in the range of 0.05-0.15 M and 0.1 M EDTA to 50 ml of a (NH4)2HPO4 solution in the range of 0.03-0.08 M. ii. Add NaOH to the solution loaded in the SVS to raise the pH to 9-13 in a controlled manner and allow to mix for a few minutes.
[0060] The inventors can apply different methods to obtain biomimetic hydroxyapatite in solution nanoflower form obtained after application of process steps i) and ii).
[0061] Obtaining nanoflower hydroxyapatite by applying microwave method iii. Treat the solution obtained in process step ii in a microwave oven, open for at least 6 hours and closed for at least 10 hours. Preferably, a 700 W oven is used as the microwave oven. iv. The mixture obtained by applying process step iii is cooled to room temperature and washed with deionized water. v. The mixture obtained by applying process step iv is dried in a vacuum oven at a temperature of at least 70° C. for at least 2 hours.
[0062] Obtaining hydroxyapatite in nanoflower form by applying sonochemical method iii. The solution obtained in process step ii is placed into an ultrasonic processing device and a mixing process is applied; The ultrasonic processing device preferably has a frequency of at least 28 kHz and a power characteristic of 200 W. iv. The mixture resulting from process step iii is exposed to ultrasonic energy for at least 90 minutes. v. The resulting hydroxyapatite compound having nanoflower-shaped morphology is then washed with deionized water and / or ethanol. vi. Then, the drying process is carried out: The drying step is preferably carried out at a temperature of at least 600° C. for a period of 24 hours.
[0063] Hydrothermal synthesis is used to obtain nanoflower-shaped hydroxyapatite. iii. The mixture obtained in process step ii is placed in a hydrothermal reactor after the mixing process; The mixing process is preferably carried out at a speed of at least 300 rpm for a period of 10 minutes. iv. The mixture obtained in process step iii is placed in a hydrothermal reactor to carry out a hydrothermal reaction; The hydrothermal reaction is carried out in the temperature range of 150-220° C. for at least 12 hours. v. The mixture is then allowed to cool to room temperature. vi. Rinse the precipitate removed from the reactor with distilled water. vii. Dry in an oven at 60°C for 24 hours.
[0064] The above manufacturing method provides a hydroxyapatite compound in the form of a nanoflower, which is then used as a component of a support phase system in the form of a nanoflower.
[0065] Synthesis of Al-Sr-OF in nanoflower morphology The support phase system of the present invention includes Al-Sr-OF and Al-Si-Sr-OF compounds as fluorine release agents. These support phase systems are usually obtained by melting methods, but their large particle size limits their use as support phase systems. The Al-Sr-OF and Al-Si-Sr-OF metal oxyfluorides with nanoflower morphology produced by the present inventors in the present invention have been used as support phase systems with hydroxyapatite in nanoflower morphology due to their excellent mechanical properties. In the nanoflower morphology, the Al-Sr-OF and Al-Si-Sr-OF compounds can be produced by three different methods, similar to the production of hydroxyapatite compounds. To apply this production method, a pre-preparation process is applied to produce the Al-Sr-OF and Al-Si-Sr-OF compounds. The process steps are as follows: i. Prepare the cation solution by mixing 80 mL of Al(NO3)9H2O in the range of 0.1-0.3 M, 20 mL of Sr(NO3)2 in the range of 0.1-0.3 M, and 0.1 M EDTA solution. ii. An anion solution is prepared by mixing 720 mL of NHOH in the range of 0.1 M to 0.3 M and 180 mL of NHF in the range of 0.1 M to 0.3 M. iii. The cation solution is added to the anion solution with vigorous stirring.
[0066] The synthesis of Al-Sr-Of compounds in nanoflower morphology is made possible by applying two different production methods, sonochemical synthesis and hydrothermal synthesis, to the mixture obtained by applying process steps i-iii.
[0067] Obtaining Al-Sr-OF with nanoflower morphology by applying sonochemical method The solution obtained by applying process step iii is stirred in an ultrasonication device at room temperature for at least 90 minutes, then the Al-Sr-OF compound in nanoflower form is synthesized. The ultrasonication device is preferably at least 28 kHz frequency and 200 W power.
[0068] Nanoflower shaped Al-Sr-OF was obtained by applying hydrothermal synthesis method. The mixture obtained in process step iii is placed in a hydrothermal reactor and subjected to a hydrothermal reaction at a temperature in the range of 150-220° C. for at least 12 hours.
[0069] Synthesis of Al-Si-Sr-OF with nanoflower morphology i. Prepare the cation solution by mixing 60-70 mL of Al(NO3)3.9H2O in the 0.1-0.3 M range with 30-40 mL of Sr(NO3)2 in the 0.1-0.3 M range and 0.1 M EDTA solution. ii. The anion solution is prepared by mixing 60-70 mL of Na2SiO3 solution in the range of 0.1-0.3 M, 600-700 mL of NH4OH solution in the range of 0.1-0.3 M, and 180 mL of 2 M NH4F solution.
[0070] The synthesis of Al-Si-Sr-Of compounds in nanoflower morphology is made possible by applying two different production methods, ultrasonic chemical synthesis and hydrothermal synthesis, to the mixture obtained by applying process steps i-ii.
[0071] Obtaining Al-Si-Sr-OF with nanoflower morphology by applying sonochemical method The solution obtained by applying process step ii is stirred in an ultrasonication device at room temperature for at least 90 minutes, then the Al-Si-Sr-OF compound in nanoflower form is synthesized. The ultrasonication device is preferably at least 28 kHz frequency and 200 W power.
[0072] Nanoflower shaped Al-Sr-OF was obtained by applying hydrothermal synthesis method. The mixture obtained in process step ii is placed in a hydrothermal reactor and subjected to a hydrothermal reaction at a temperature in the range of 150-220° C. for at least 12 hours.
[0073] Silica Synthesis Silica powder was obtained on a rotary evaporator using Ludox HS-40, a colloidal silica solution for commercial use, in the support phase system. The experimental steps carried out are outlined below: i. Place 100 mL of the colloidal silica solution into the 250 mL glass chamber of a rotary evaporator. ii. In the drying process, the temperature is gradually decreased from 160°C to 40°C. iii. The temperature is fixed at 40°C and drying is continued for 3 hours. iv. The dried silica powder is mechanically ground using a ball mill for 24 hours. v. The ground powder is passed through a 250 mesh sieve and used as the supporting phase.
[0074] The support phase system of the present invention is preferably subjected to a silanization process to obtain a silanized support phase system. A preferred embodiment of the present invention is to combine the support phase component powders obtained by the manufacturing method shown in the present invention and subject them to a silanization process.
[0075] Silanization of the supporting phase system Silanization of the support phase system is carried out in a nitrogen atmosphere according to the following steps, respectively: i. In a sealed glass bottle, add 5% to 10% by weight of 3-methacryloyloxypropyltrimethoxysilane to a solution of ethanol:water in a weight ratio of 4:1 to 10:1, adjust the pH of the solution to a value in the range of 3 to 4 with acetic acid solution, and mix at room temperature for 1 hour. ii. The support phase system to be modified is then added to this solution under vigorous stirring and stirred for 24 hours at room temperature. iii. After silane inoculation, the reaction mixture is filtered and rinsed with ethanol to remove physically adsorbed silane. iv. This process is followed by drying at 60°C to increase the concentration of silanol molecules and remove residual solvent.
[0076] The dental filling material of the present invention is a composite material and comprises at least one supporting phase and a matrix component. All of the components used as the matrix component in the present invention are derived from organic compounds.
[0077] Synthesis of organic matrices The experimental steps followed during the preparation of the organic matrix and the CQ, TPO, and 4-EDMAB components used as photoinitiators, carried out in the designated steps, are described below. i. Preheat BisGMA and TEGDMA by placing them in a 37° C. oven. ii. Weigh out BisGMA and TEGDMA on a precision scale and place in the Speedmixer container for mixing. iii. CQ, TPO, and a photoinitiator called 4-EDMAB are weighed out on a precision scale to adhere to the composition ratio so that the dental composite produced can be cured with a blue light photocuring device. iv. The organic phase and photoinitiator are placed in the same vessel and stirred vigorously at 2000 rpm for three 5 minute intervals.
[0078] Synthesis of acrylic dental composite fillings i. 1 wt % to 5 wt % BisGMA is stirred in an ultrasonic water bath at constant temperature for 10 minutes. ii. The organic resin portion of the composite structure is prepared by adding TEGDMA in the range of 1% to 5% by weight to the mixture obtained in process step i). iii. Camphorquinone in the range of 0.05 wt% to 0.2 wt% and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide compound in the range of 0.05 wt% to 0.2 wt% as photoinitiators and 4-EDMAB compound in the range of 0.5 to 1 wt% as activator are added to the organic resin mixture obtained in process step ii) and the mixture is heated for 10 minutes. iv. The supporting phase system and composite fillers in a weight ratio of 50-90% relative to the organic resin mixture obtained in process step iii) are mixed as a result of a mixing process in an ultrasonic water bath or by a high-speed mixer for at least one day until a homogenous mixture is obtained. The support phase system includes a hydroxyapatite compound having a nanoflower morphology, an Al-Si-Sr-OF compound having a nanoflower morphology, an Al-Sr-OF compound having a nanoflower morphology, and a silica compound. v. The composite filling material obtained in process step iv is brought back to room temperature and put into a Teflon mold with a spatula, and a curing process is applied using a blue LED light device.
[0079] The use of hydroxyapatite, Al-Sr-OF, and Al-Si-Sr-OF support phase systems with nanoflower morphology in restorative dental composites, either individually or in combination, is new in the art. This allows for composite fillings with biocompatibility, antibacterial properties, and improved mechanical properties compared to dental composites of the art. Nanodimensional support phase systems with high surface reactivity and surface area / volume ratios are obtained by the nanoflower morphology obtained in more sensitive process steps compared to current methods. As a result, the hydroxyapatite, Al-Sr-OF, and Al-Si-Sr-OF support phase systems with nanoflower morphology improve the regenerative and antibacterial properties of the composite fillings, and also improve their mechanical properties. Thus, the mechanical, physical, chemical, and antibacterial properties of dental composite fillings with BHA, Al-Sr-OF, and Al-Si-Sr-OF support phases with nanoflower morphology formed by the overall combination of nano-sized rods can be simultaneously optimized. This application allows minerals and elements of the original structure of the tooth to be synthesized so that they have a nanoflower morphology and added to dental composite structures. By overcoming the biggest obstacle in this situation to date, the problem of low mechanical strength, a filling material can be produced that is different and more advantageous than the current proposed solutions.
[0080] The scope of protection of the present invention is set forth in the appended claims and cannot be limited to the sample described in this detailed description. In view of the above facts, it is obvious that a person skilled in the art can provide similar embodiments without departing from the subject matter of the present invention.
Claims
1. An acrylic dental composite filling material comprising a photocurable and polymerizable organic compound, a photoinitiator, and a supporting phase system, - a hydroxyapatite component with nanoflower morphology that confers regenerative properties to the composite filler in the support phase system; a compound comprising Al-Si-Sr-OF and Al-Sr-OF fluorides with nanoflower morphology as a supporting phase system for imparting antibacterial properties to the composite filler in said supporting phase system; a silica component within the support phase system; a mixture of BisGMA and TEGDMA compounds as organic compounds; A composite filler comprising, as a photoinitiator, at least one member selected from the group consisting of CQ, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, 1-phenyl-1,2-propanedione, and 4-EDMAB.
2. 2. The composite filler of claim 1, wherein the BisGMA is in the range of 1 to 5 wt.%.
3. 2. The composite filler of claim 1, wherein the TEGDMA is in the range of 1 to 5 wt. %.
4. The composite filler according to claim 1, characterized in that the CQ is in the range of 0.1-0.5 wt%.
5. 2. The composite filler of claim 1, wherein the diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide is in the range of 0.1 to 0.5 wt %.
6. 2. The composite filler of claim 1, wherein the 1-phenyl-1,2-propanedione is in the range of 0.1 to 0.5 wt %.
7. 2. The composite filler of claim 1, wherein the 4-EDMAB is in the range of 0.5 to 1.0 wt %.
8. 2. The composite filler of claim 1, wherein the amount of said supporting phase system is in the range of 50% to 90% by weight.
9. A composite filler according to any one of the preceding claims, characterized in that in addition to the organic compound and the supporting phase system it further comprises a pigment.
10. The composite filler of claim 11, wherein the pigment is present in an amount of 0.01 to 1% by weight.
11. The pigments are Duranat Yellow Iron Oxide (Pigment Yellow 42 & 43 CI 77492), Duranat Red Iron Oxide (Pigment Red 101 CI 77491), Phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 1-phenyl-1,2-propanedione 98%, Diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, Duranat Brown Iron Oxide (Pigment Brown), Duranat Black Iron Oxide (Pigment Black 11 CI 77499), Iron Oxide (FeO-Red), Iron Hydroxide (FeOOH-Yellow), TiO, E171 Titanium Dioxide, Pigment White 6 11. Composite filler according to any one of claims 9 to 10, characterized in that it is selected from the group consisting of: CI 77891, CI 77891, or mixtures thereof.
12. A method for producing the light curable and polymerizable antibacterial restorative acrylic dental composite filling material according to any one of claims 1 to 11, comprising the following process steps: i. agitating 1 wt% to 5 wt% of BisGMA in an ultrasonic water bath at constant temperature; ii. the organic resin portion of the composite structure is prepared by adding TEGDMA to the mixture obtained in process step i) in the range of 1% to 5% by weight; iii. adding camphorquinone in the range of 0.05% to 0.2% by weight and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide compound in the range of 0.05% to 0.2% by weight as photoinitiators and 4-EDMAB compound in the range of 0.5 to 1% by weight as activator to the organic resin mixture obtained in process step ii) and heating said mixture for 10 minutes; iv. The support phase system and the composite filler in a weight ratio of 50-90% by weight relative to the organic resin mixture obtained in process step iii) are obtained as a result of a mixing process in the ultrasonic water bath or by a high speed mixer until a homogenous mixture is obtained, the support phase system comprises the hydroxyapatite compound having a nanoflower morphology, the Al—Si—Sr—OF compound having a nanoflower morphology, the Al—Sr—OF compound having a nanoflower morphology, and the silica compound; v. placing said composite filler obtained in process step iv) into a Teflon mold with a spatula by allowing it to cool to room temperature; vi) the curing process is applied using a blue LED light device.
13. 13. A method for producing an acrylic dental composite filling according to claim 12, characterized in that in process step i) the mixing step is carried out at 40° C. for 10 minutes.
14. 14. A method for producing an acrylic dental composite filling according to any one of claims 12 to 13, characterized in that the supporting phase system is added in process step iv) in a proportion of 70%.
15. 15. A method for producing an acrylic dental composite filling according to any one of claims 12 to 14, characterized in that the mixing step is carried out in process step iii) for 3 hours.
16. 16. A method for producing an acrylic dental composite filling according to any one of claims 12 to 15, characterized in that the mixing step is carried out in process step iv) for one day.
17. 17. A method for producing an acrylic dental composite filling according to any one of claims 12 to 16, characterized in that the treatment process with the blue LED light device is carried out for 20 seconds in process step vi).
Citation Information
Patent Citations
Method of preparing hydroxyapatite with three-dimensional nanoflower structure
CN102556993A
Use of nanoparticles to adjust the refractive index of dental compositions
JP2007538072A
Use of nanoparticles to adjust refractive index of dental compositions
US20050252414A1
Production of antibacterial and regenerative dental composite using supportive phases (fillers) antibacterial and bioactive properties of which are improved
WO2019132849A2